Proceedings of the Web Conference 2020 2020
DOI: 10.1145/3366423.3380223
|View full text |Cite
|
Sign up to set email alerts
|

What Changed Your Mind: The Roles of Dynamic Topics and Discourse in Argumentation Process

Abstract: In our world with full of uncertainty, debates and argumentation contribute to the progress of science and society. Despite of the increasing attention to characterize human arguments, most progress made so far focus on the debate outcome, largely ignoring the dynamic patterns in argumentation processes. This paper presents a study that automatically analyzes the key factors in argument persuasiveness, beyond simply predicting who will persuade whom. Specifically, we propose a novel neural model that is able t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 36 publications
0
12
0
1
Order By: Relevance
“…The closest semblance to our work in NLP literature ties in with argumentation, be it essays (Carlile et al, 2018), debates (Cano-Basave andHe, 2016), or discussions on social media platforms (Al-Khatib et al, 2018;Zeng et al, 2020). Such works have revolved mostly on analysing argumentative strategies and their effect on others.…”
Section: Related Workmentioning
confidence: 86%
“…The closest semblance to our work in NLP literature ties in with argumentation, be it essays (Carlile et al, 2018), debates (Cano-Basave andHe, 2016), or discussions on social media platforms (Al-Khatib et al, 2018;Zeng et al, 2020). Such works have revolved mostly on analysing argumentative strategies and their effect on others.…”
Section: Related Workmentioning
confidence: 86%
“…In addition to the features mentioned above, the role of pragmatic and discourse contexts has shown to be crucial by not yet fully explored. Zeng et al (2020) examined how the contexts and the dynamic progress of argumentative conversations influence the comparative persuasiveness of an argumentation process. created a new dataset based on argument claims and impact votes from a debate platform kialo.com, and experiments showed that incorporating contexts is useful to classify the argument impact.…”
Section: Related Workmentioning
confidence: 99%
“…Bosc et al (2016) proposes a dataset of Social Media data with coarse topic labels extracted from the hashtags (e.g., #Ap-pleWatch). Zeng et al (2020) designed a model to encode the latent topics of argumentative conversations. Unlike the previous work, our work studies the effect of argument topic for structured debates explicitly for predicting persuasion.…”
Section: Related Workmentioning
confidence: 99%